Infrared suppression of a power-generation cabin with a cold plate system. (25th July 2019) - Yang, Fan; Lin, Yang; Wei, Xuezhong; Ye, Hong
Highlights: Cold plate system for infrared suppression of power-generation cabin is proposed. Louvered cold plate is proposed and designed as the exhaust side. The simulated results agreed well with the experimental ones. Infrared suppression effect of the cold plate system is discussed and evaluated. Cold plate system is effective in infrared suppression. Abstract: It is found through experimental investigation that, when a power-generation cabin is operating, the infrared signature of the exhaust side is the most prominent, while that of the front, top and back sides (lateral sides) are also strong. To suppress the infrared signature, a cold plate system is conceived to isolate the high temperature genset, in which flat cold plates are adopted as the lateral sides and a louvered cold plate is designed as the exhaust side. A simulation model of the power-generation cabin with the cold plate system is established and experimentally verified, and it is applied to optimize the layout of the flat cold plates and the blade inclination and tube spacing of the louvered cold plate. The experimental result shows that the infrared suppression effect of the optimized cold plate system is convincing. The simulation results indicate that when adopting the cold plate system, the maximal temperature difference between the lateral sides and the ambient air decreases from 28.57 °C to 0.98 °C, while the corresponding value for the exhaust side decreases from 34.76 °C to 5.17 °C, significantly suppressing the infrared signature of the power-generation cabin.